Implementation of Tourism Policies in the Development of Jerowaru Tourism Village, East Lombok - Karyadi, Lalu Wiresapta; Muktasam, Muktasam; Wijayanti, Ika; Hakim, Latifa Dinar Rahmani (Baileo: Jurnal Sosial Humaniora, 2024)
This study aims to examine the implementation of tourism policies in the development of Jerowaru Tourism Village, East Lombok, as a strategic initiative for rural empowerment and poverty alleviation in coastal areas. Using a qualitative case study method and grounded in Woolcock’s social capital theory, this research involved field observations, in-depth interviews with community stakeholders, and documentation analysis. The findings reveal that policy implementation aligns with various national and regional regulations, including the Tourism Law, Regional Autonomy Law, and the 2021 NTB Governor Regulation. Three key dimensions support the tourism village policy: (1) coordination, communication, and disposition among stakeholders; (2) the active role of youth-driven tourism awareness groups (Pokdarwis) in fostering community participation; and (3) grassroots initiatives that emphasize environmental sustainability and local identity. The tourism village has leveraged the 3A framework—Attractions, Amenities, and Accessibility—while empowering local actors to lead management and innovation. The novelty of this study lies in demonstrating how social capital functions as a bridge between policy implementation and grassroots empowerment, enhancing both community capacity and local economic resilience. The research recommends stronger multi-stakeholder collaboration and targeted policy support to reinforce tourism-based village development models within broader social science and humanities discourse.